2018
DOI: 10.1108/qram-01-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the temporal dimension of legitimisation strategies

Abstract: Purpose The purpose of this study is to examine how social disclosures by one of the world’s largest producers of Platinum Group Metals are used to maintain and repair legitimacy in the context of South Africa’s prevailing socio-economic conditions and in response to the immediate challenge to legitimacy posed by violent worker demonstrations taking place at its operations in Marikana during August 2012. This is done to highlight how legitimacy strategies take account of the temporal characteristics of a threa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 65 publications
(230 reference statements)
0
10
0
Order By: Relevance
“…In setting the context for evaluating OHS accountability in the Covid-19 era, it is also instructive to briefly reflect on what prior research literature has revealed about motivations for CSR disclosure in general. Generally, studies have suggested that firms engage in CSR for improved financial outcomes (Aguilera et al , 2007; Mackey et al , 2007; Margolis et al , 2009; Pava and Krausz, 1996); altruistic reasons (Parker, 2014) or philanthropic reasons (Acharyya and Agarwala, 2020); reputation and competitive advantage (Zhang et al , 2019; Albinger and Freeman, 2000; Falkenberg and Brunsæl, 2011; Lii and Lee, 2012; McWilliams and Siegel, 2001), based on intrinsic and/or extrinsic motivations (Grimstad et al , 2020) or for legitimation purposes (Maroun, 2018). The literature examining the link between financial performance and social performance has a history of more than three decades (Margolis et al , 2009).…”
Section: A Brief History and More Recent Corporate Social Responsibil...mentioning
confidence: 99%
“…In setting the context for evaluating OHS accountability in the Covid-19 era, it is also instructive to briefly reflect on what prior research literature has revealed about motivations for CSR disclosure in general. Generally, studies have suggested that firms engage in CSR for improved financial outcomes (Aguilera et al , 2007; Mackey et al , 2007; Margolis et al , 2009; Pava and Krausz, 1996); altruistic reasons (Parker, 2014) or philanthropic reasons (Acharyya and Agarwala, 2020); reputation and competitive advantage (Zhang et al , 2019; Albinger and Freeman, 2000; Falkenberg and Brunsæl, 2011; Lii and Lee, 2012; McWilliams and Siegel, 2001), based on intrinsic and/or extrinsic motivations (Grimstad et al , 2020) or for legitimation purposes (Maroun, 2018). The literature examining the link between financial performance and social performance has a history of more than three decades (Margolis et al , 2009).…”
Section: A Brief History and More Recent Corporate Social Responsibil...mentioning
confidence: 99%
“…However, most studies draw on case studies (Contrafatto & Burns, 2013; Le Breton & Aggeri, 2019; Leong & Hazelton, 2019; Li & Belal, 2018) or qualitative interviewing (Albelda-Pérez et al, 2007; Rodríguez-Gutiérrez et al, 2019; Stubbs & Higgins, 2014) as their empirical methods. Methods where the researcher has a less interventionist role, such as questionnaires (Arjaliès & Mundy, 2013), discourse analysis (Tregidga et al, 2014), or thematic content analysis (Maroun, 2018), are also applied.…”
Section: Mapping the Literature On Sustainability Accounting And Repo...mentioning
confidence: 99%
“…The findings in most of those studies suggest that SAR practices informing internal decision-making have the potential to foster organizational change. This finding might be explained because the incorporation of SAR in internal decision-making could be indicative of an authentic organizational commitment, with a concomitant reflection in core beliefs and values that are inscribed in the organization (i.e., their DNA ), while changing these schemes through external SAR (i.e., sustainability reporting) has generally proved to be difficult (Larrinaga and Bebbington, 2001; Maroun, 2018; Stubbs & Higgins, 2014). However, different studies have argued that sustainability reporting could also drive sustainable organizational change when it is mandatorily required (Leong & Hazelton, 2019), or when it is associated with integrated reporting (Cerbone & Maroun, 2020; Le Roux & Pretorius, 2019; McNally & Maroun, 2018), as integrated thinking aims to broaden the value perspective of organizations to align value creation with broader sustainability concerns.…”
Section: Mapping the Literature On Sustainability Accounting And Repo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Companies are facing increased pressure from shareholders and regulatory authorities to respond to social and environmental concerns, and consider them as part of their business models (Maroun, 2018). As business entities continue to increase their level of operations across international borders, their conduct on the sustainable development front instigates even greater concern.…”
Section: Introductionmentioning
confidence: 99%